1995
DOI: 10.1021/bi00042a012
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of the phase preferences of the major lipids of the Acholeplasma laidlawii B membrane

Abstract: We have quantitated the phase preferences of all of the quantitatively significant lipids of fatty acid-homogeneous Acholeplasma laidlawii membranes by determining the effect of small amounts of each lipid on the lamellar/reversed hexagonal phase transition temperature of a phosphatidylethanolamine matrix of identical fatty acid composition using differential scanning calorimetry. We find that the incorporation of small amounts of these lipids produce effects ranging from a moderate depression to a marked elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
(43 reference statements)
0
28
0
Order By: Relevance
“…2 and 3, MGDRG is more abundant at +5 °C near the optimal growth temperature and DGDRG, which is present at −5 °C, is essentially absent at this temperature. The phase behavior of a monoglucosyldiacylglycerol (MGDG) and a diglucosyldiacylglycerol (DGDG) have been studied intensively in Acholeplasma laidlawii [2729]. In a classic study on phase equilibria of total membrane lipids from this organism, it was shown that as the degree of unsaturation of the membrane lipids was varied from approximately 20% to over 90% cis -9–18:1 (oleic acid), the ratio of DGDG/MGDG increased from 0.59 to 5.6.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3, MGDRG is more abundant at +5 °C near the optimal growth temperature and DGDRG, which is present at −5 °C, is essentially absent at this temperature. The phase behavior of a monoglucosyldiacylglycerol (MGDG) and a diglucosyldiacylglycerol (DGDG) have been studied intensively in Acholeplasma laidlawii [2729]. In a classic study on phase equilibria of total membrane lipids from this organism, it was shown that as the degree of unsaturation of the membrane lipids was varied from approximately 20% to over 90% cis -9–18:1 (oleic acid), the ratio of DGDG/MGDG increased from 0.59 to 5.6.…”
Section: Discussionmentioning
confidence: 99%
“…In the cell wall-less bacterium Acholeplasma laidlawii, MGlcDG is the most abundant lipid and occupies about one-half of its membrane (Foht et al, 1995). In Bacillus subtilis, MGlcDG is about 10% of the total lipid (Matsumoto et al, 1998).…”
mentioning
confidence: 99%
“…The purpose is to maintain (i) phase equilibria close to a potential bilayer/nonbilayer transition (5), (ii) a nearly constant radius of spontaneous curvature (6), and (iii) a constant (anionic) surface charge density (7) for the membrane lipid bilayer mixture. Similar packing properties are also maintained in other bacteria by regulation especially at the acyl chain level, like Escherichia coli (8, 9), Clostridium butyricum (10), and Bacillus megaterium (11), the latter two also by some extent of polar head group changes.The regulation of the packing properties is mainly accomplished by altering the relative proportions of MGlcDAG and DGlcDAG, forming essentially nonlamellar and lamellar phases (5,(12)(13)(14). In vivo, parameters giving more nonlamellar properties to the bilayer, like higher growth temperature and more of longer and unsaturated acyl chains, result in an increase of the DGlcDAG fraction and a decrease of the MGlc-…”
mentioning
confidence: 99%
“…The regulation of the packing properties is mainly accomplished by altering the relative proportions of MGlcDAG and DGlcDAG, forming essentially nonlamellar and lamellar phases (5,(12)(13)(14). In vivo, parameters giving more nonlamellar properties to the bilayer, like higher growth temperature and more of longer and unsaturated acyl chains, result in an increase of the DGlcDAG fraction and a decrease of the MGlc-…”
mentioning
confidence: 99%